Students' perception of problems and benefits of night shift nursing internship: A qualitative study - Farhad Bahramirad; Narjes Heshmatifar; Mostafa Rad (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Recently, the night shift is included in the curriculum of nursing internship students. However, this shift is associated with some problems and benefits for students, which have been assessed in limited studies. This study aimed to discover and describe the problems and benefits of the night shift for nursing internship students. METHODOLOGY: This qualitative method was carried out with the conventional content-analysis method. In total, 15 seventh-semester and eighth-semester nursing students at Sabzevar University of Medical Sciences, Iran, were selected by purposeful sampling. Data were collected using in-depth semi-structured interviews about students' perceptions of night shift problems and benefits. In addition, data analysis was performed applying the conventional content-analysis technique. RESULTS: In this study, seven main categories were extracted, five of which included problems such as exploitations, being an outsider, moral distress, learning deficits, and annoyance. The other two categories were benefits including gaining new experiences and independence. CONCLUSION: The problems related to the students were the nursing personnel and the educational system of hospitals, which can be dealt with through the interaction of the educational system with hospitals managers in order to clarifying the role of students, fair division of work, and making educational resources available. Moreover, gaining new experiences and independence are among the benefits of the night shift for students, the continuation of which is in favor of nursing education.